The Heaven & Earth Grocery Store - McBride, James, 1957- (New York : Riverhead Books, 2023)
"In 1972, when workers in Pottstown, Pennsylvania, were digging the foundations for a new development, the last thing they expected to find was a skeleton at the bottom of a well. Who the skeleton was and how it got there were two of the long-held secrets kept by the residents of Chicken Hill, the dilapidated neighborhood where immigrant Jews and African Americans lived side by side and shared ambitions and sorrows. Chicken Hill was where Moshe and Chona Ludlow lived when Moshe integrated his theater and where Chona ran the Heaven & Earth Grocery Store. When the state came looking for a deaf boy to institutionalize him, it was Chona and Nate Timblin, the Black janitor at Moshe's theater and the unofficial leader of the Black community on Chicken Hill, who worked together to keep the boy safe. As these characters' stories overlap and deepen, it becomes clear how much the people who live on the margins of white, Christian America struggle and what they must do to survive. When the truth is finally revealed about what happened on Chicken Hill and the part the town's white establishment played in it, McBride shows us that even in dark times, it is love and community--heaven and earth--that sustain us."--
Keywords: Ku Klux Klan (1915- ) -- Fiction; African Americans -- Fiction; Jews -- Fiction; Deaf -- Fiction; Murder -- Investigation -- Fiction; Pennsylvania -- Fiction; Historical fiction; Novels